1999
DOI: 10.1034/j.1399-3003.1999.14a24.x
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral blood cytokine responses and disease severity in respiratory syncytial virus bronchiolitis

Abstract: The role of cellular immunity in disease severity in respiratory syncytial virus (RSV) bronchiolitis is largely unknown. This study investigated the association between disease severity and systemic cytokine responses in hospitalized ventilated and nonventilated RSV bronchiolitis patients.In whole blood cultures stimulated with phytohaemagglutinin (PHA), lymphoproliferative responses and interferon (IFN)-c and interleukin (IL)-4 production during acute illness were measured. In addition, plasma cytokines were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
78
1
10

Year Published

2000
2000
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(100 citation statements)
references
References 34 publications
11
78
1
10
Order By: Relevance
“…Several clinical studies have indicated a correlation of decreased IL-12 with severe cases of RSV-induced airway disease (46,55,56). These findings, along with a number of animal studies in allergy/asthma, suggest that this cytokine axis may play a significant role in determining the overall direction of the pulmonary response.…”
Section: Discussionmentioning
confidence: 70%
“…Several clinical studies have indicated a correlation of decreased IL-12 with severe cases of RSV-induced airway disease (46,55,56). These findings, along with a number of animal studies in allergy/asthma, suggest that this cytokine axis may play a significant role in determining the overall direction of the pulmonary response.…”
Section: Discussionmentioning
confidence: 70%
“…However, the Th1/Th2 balance, as explanatory model for the pathogenesis of the RSV infection, is not absolute and has been contradicted by several human studies in which a Th2 predominance (21)(22)(23)(24)(25) and/or a decreased Th1 response (22,23,25) were not confirmed, implying that different mechanisms are involved in the immune-mediated events during severe RSV bronchiolitis.…”
Section: Th1 Cells Th2 Cells and Rsvmentioning
confidence: 97%
“…Additionally, in a bovine model RSV infection has been shown to enhance sensitization to subsequent airway Ag (61,62). Although still controversial, a variety of studies suggest that individuals who suffered an RSV infection during childhood are significantly predisposed to develop allergy and atopy either during early adulthood or later (63)(64)(65)(66)(67)(68)(69)(70).…”
Section: Discussionmentioning
confidence: 99%